Differential expression of mTOR components in endometriosis and ovarian cancer: Effects of rapalogues and dual kinase inhibitors on mTORC1 and mTORC2 stoichiometry - Rogers-Broadway,K-R; Kumar,J; Sisu,C; Wander,G; Mazey,E; Jeyaneethi,J; Pados,G; Tsolakidis,D; Klonos,E; Grunt,T; Hall,M; Chatterjee,J; et al. (International Journal of Molecular Medicine, 2019)
Endometriosis is a wellknown risk factor for ovarian cancer. The genetic changes that characterise endometriosis are poorly understood; however, the mechanistic target of rapamycin (mTOR) pathway is involved. In this study, we investigated the expression of key mTOR components in endometriosis and the effects of rapalogues using an endometrioid ovarian carcinoma cell line (MDAH 2774) as an in vitro model. Gene expression of mTOR, DEPTOR, Rictor and Raptor was assessed by qPCR in 24 endometriosis patients and in silico in ovarian cancer patients. Furthermore, the effects of Rapamycin, Everolimus, Deforolimus, Temsirolimus, Resveratrol, and BEZ235 (Dactolisib, a dual kinase inhibitor) on mTOR signalling components was assessed. mTOR showed a significant increase in the expression in endometriosis and ovarian endometrioid adenocarcinoma patients compared to nonaffected controls. DEPTOR, an inhibitor of mTOR, was downregulated in the advanced stages of ovarian cancer (III and IV) compared to earlier stages (I and II). Treatment of MDAH2774 cells with the mTOR inhibitors resulted in the significant upregulation of DEPTOR mRNA, whereas treatment with rapamycin and BEZ235 (100 nM) resulted in downregulation of the mTOR protein expression after 48 h of treatment. None of the treatments resulted in translocation of mTOR from cytoplasm to nucleus. Upregulation of DEPTOR is a positive prognostic marker in ovarian cancer and is increased in response to mTOR pathway inhibition suggesting that it functions as a tumour suppressor gene in endometrioid ovarian carcinoma. Collectively, our data suggest the mTOR pathway as a potential connection between endometriosis and ovarian cancer and may be a potential target in the treatment of both conditions.